PREPARATION, EVALUATION, AND CLINICAL APPLICATION OF SAFFLOWER CREAM AS TOPICAL NUTRITIVE AGENT - Dakhil, Ibtihal Abdulkadhim; Abbas, Ibrahim S; Marie, Nidhal K (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to formulate and evaluate safflower seeds oil as herbal nutritive skin cream and to study its clinical effect. Methods: After collecting the safflower seeds, the oil was extracted using an expeller or cold pressing. Physical parameters of oil were determined. Determination of unsaturated fatty acids was done by gas-liquid chromatography (GLC). The oil is then placed in an emulsifier to form cream using various additives and all formulas evaluated according to physical properties, PH, and viscosity. All symptoms such as skin damage by sunlight, skin aging, oxidative damage after sunburn or after chemical treatments, all of these conditions have recovered. Statistical data analysis was carried out using Statistical Analysis System, and all recorded data for analysis of variance and least significant difference were at least the significant difference at level 0.01. Results: The results of the GLC analysis indicated that safflower oil contains five different fatty acids, including linoleic acid (56.37%), linolenic acid (15.02%), stearic acid (2.37%), oleic acid (14.83%), and palmitic acid (7.91%). Refractive index values, density, and specific gravity were 1.476, 0.921 g/cm3, and 0.925, respectively. The results of a clinical study showed the effect of safflower cream as an antioxidant which protected the skin in particular from oxidative damage after sunburn and reduced the symptoms of skin aging. This effect was evident in both concentrations 10% and 15% when compared with control. Control response rate, 10% of safflower cream, and 15% of safflower cream were reached to 76%, 85%, and 92% within 2 weeks of treatment, respectively. Conclusion: The study showed the importance of safflower oil as a source of omega-3 and contains various unsaturated fatty acids which act as an antioxidant to restore skin health and aging resistance. This study approved that safflower oil characteristics can make it the main ingredients in the preparation of topical agents for the treatment of various skin problems.